Trabectedin as a single agent and in combination with pegylated liposomal doxorubicin – activity against ovarian cancer cells - Marczak, Agnieszka; Denel, Marta (Contemporary Oncology/Współczesna Onkologia, 2014)
Over 225 000 new cases of ovarian cancer are diagnosed each year. Symptoms are often vague, so most cases are detected when the disease is at an advanced stage. There is a need to find new drugs which will be able to treat ovarian cancer effectively. One of the most promising antineoplastic agents is trabectedin (Yondelis), derived from the marine tunicate Ecteinascidia turbinata, approved by the European Union in July 2007 for the treatment of soft-tissue sarcomas. This drug shows a mechanism of action based on the inhibition of the nucleotide excision repair system. Trabectedin shows anti-tumour activity in vitro and in vivo in ovarian, breast, prostate, renal, melanoma and non-small cell lung cancer cell lines. Trabectedin in combination with pegylated liposomal doxorubicin demonstrates synergistic antineoplastic activity.